A randomized trial of blended first aid education for the public (International Journal of First Aid Education)
First aid educators are increasingly experimenting with blending learning modalities, combining asynchronous internet based (e-learning) and traditional instructor led (face-to-face). This study seeks to validate the effectiveness of using e-learning followed by face-to-face learning in first aid education to improve laypersons’ knowledge, confidence, and willingness, compared to face-to-face only learning.Method: 128 non-healthcare adult volunteers (laypeople) were randomly assigned to either a face-to-face (control, n=58) or a blended (experimental, n=70) British Red Cross Everyday First Aid course. The effectiveness of learning was measured through pre- and post-learning evaluation forms using 0-10 Likert scales and questions on first aid knowledge for both face-to-face and blended groups, and additionally, post-online (blended learners only).Results: We found comparable results between face-to-face and blended learning for improving learner knowledge of first aid. Blended learners were found to have increased confidence and willingness than face-to face learners. In the blended cohort, knowledge appears to increase most during the online phase, but this is not mirrored for confidence or willingness. Discussion: Blended learning appears to be comparable to face-to-face only learning for first aid education for learner outcomes of knowledge, and superior for increasing confidence and willingness in the study sample. Providing an alternative learning modality can allow more flexibility for those providing and those joining first aid courses. An implication of this study is the potential for educators to offer different learning opportunities according to learner preference.